Structural response of steel lined pipes under cyclic bending. (January 2022) - Gavriilidis, Ilias; Karamanos, Spyros A.
Abstract: Motivated by reeling installation of mechanically-lined offshore steel pipes, the present paper investigates the structural performance of a bi-material lined pipe under cyclic bending, using advanced finite element tools. A three-dimensional finite element model is developed, simulating the manufacturing process of the lined pipe in the first stage of the analysis, followed by the cyclic bending response of the lined pipe in the second stage. Five bending cycles are considered, representing the two installation cycles and three additional cycles of a failure-repair scenario. The loading cycles impose a bending curvature range corresponding to the strains developed during a typical reeling installation process. Different loading patterns are considered and their effect on liner performance are investigated. The results show that the application of reverse (negative) curvature during the loading cycles, representing the straightener, has a significant influence on the wrinkle size of the liner developed at the two critical generators, and its rate of increase, compared with cyclic bending patterns with non-negative curvature. Numerical results on imperfection sensitivity are obtained, considering two types of imperfection of the liner pipe. In addition, the structural performance of liners with different thickness is examined, and the results show that there exists a minimum value of wall thickness, above which the liner does not exhibit local buckling at the end of the cyclic loading history. The beneficial effect of internal pressure on liner cyclic response is also verified, especially for thin-walled liners, preventing the development of wrinkles. Finally, the effect of manufacturing process is examined, showing the superior structural performance of partially-heated lined pipes, with respect to fully-heated lined pipes, and to lined pipes manufactured by purely-mechanical process.